Genetic effects on information processing speed are moderated by age – converging results from three samples. (8th April 2014) - Ising, M.; Mather, K. A.; Zimmermann, P.; Brückl, T.; Höhne, N.; Heck, A.; Schenk, L. A.; Rujescu, D.; Armstrong, N. J.; Sachdev, P. S.; Reppermund, S.
Abstract : Information processing is a cognitive trait forming the basis of complex abilities like executive function. The Trail Making Test (TMT) is a well‐established test of information processing with moderate to high heritability. Age of the individual also plays an important role. A number of genetic association studies with the TMT have been performed, which, however, did not consider age as a moderating factor. We report the results of genome‐wide association studies (GWASs) on age‐independent and age‐dependent TMT performance in two population‐representative community samples (Munich Antidepressant Response Signature, MARS: N 1  = 540; Ludwig Maximilians University, LMU: N 2  = 350). Age‐dependent genome‐wide findings were then evaluated in a third sample of healthy elderly subjects (Sydney Memory and Ageing Study, Sydney MAS: N 3  = 448). While a meta‐analysis on the GWAS findings did not reveal age‐independent TMT associations withstanding correction for multiple testing, we found a genome‐wide significant age‐moderated effect between variants in the DSG1 gene region and TMT‐A performance predominantly reflecting visual processing speed (rs2199301, P meta‐analysis  = 1.3 × 10 −7 ). The direction of the interaction suggests for the minor allele a beneficial effect in younger adults turning into a detrimental effect in older adults. The detrimental effect of the missense single nucleotide polymorphism rs1426310 within the same DSG1 gene region could be replicated in Sydney MAS participants aged 70–79, but not in those aged 80 years and older, presumably a result of survivor bias. Our findings demonstrate opposing effects of DSG1 variants on information processing speed depending on age, which might be related to the complex processes that DSG1 is involved with, including cell adhesion and apoptosis. Abstract : Our GWAS findings demonstrate opposing effects of DSG1 variants on information processing speed depending on the age of the individual.